The Role of Intrinsic Motivation in Mediating the Influence of Asta Brata Leadership And Organizational Culture Based on Tri Hita Karana on Employee Performance at Village Credit Institutions in Kuta Sub-District - Ni Luh Yuni KARTIKA; I Made SARA; Gusti Ayu SUGIATI (PT Keberlanjutan Strategis Indonesia, 2025)
Lembaga Perkreditan Desa (LPD) is a customary law-based financial institution that strategically supports the economy of village communities in Bali, especially through financial services for MSMEs and local residents. Although the presence of LPDs in Bali is almost evenly distributed, with 1,437 units from 1,485 traditional villages, the performance of some LPDs has decreased due to competition with other financial institutions and the emergence of legal cases involving their administrators. This study analyzes the influence of Asta Brata leadership and Tri Hita Karana-based organizational culture on the performance of LPD employees in Kuta District, with intrinsic motivation as a mediating variable. A sample of 69 respondents was randomly determined using the Slovin formula. Data were collected through questionnaires and analyzed using Partial Least Square (PLS). The results showed that Asta Brata leadership had a significant positive effect on performance but did not significantly affect intrinsic motivation. Tri Hita Karana organizational culture significantly positively affects employee performance and intrinsic motivation. Intrinsic motivation is proven to have a significant positive effect on performance and partially mediates the effect of Tri Hita Karana organizational culture on performance but does not mediate the effect of Asta Brata leadership on performance. These findings support the attribution theory that internal (motivation, leadership) and external (work culture) factors influence employee performance. This study emphasizes the importance of strengthening local values ​​in leadership and organizational culture and effective HR management to maintain the sustainability of LPD.